1989
DOI: 10.1111/j.1600-051x.1989.tb01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of complement cleavage in gingival fluid during experimental gingivitis in man

Abstract: The cleavage of complement may be an important immunopathologic mechanism in the development of gingival inflammation. Utilizing the experimental gingivitis model, cleavage of C3, C4 and B was assessed in gingival fluid following abstention from oral hygiene. 4 male dental students performed stringent oral hygiene measures until the gingival index approached 0, then refrained from any oral hygiene for 21 days. Gingival fluid, sampled with filter paper strips from the mesial surface of all maxillary premolars a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 23 publications
5
68
0
1
Order By: Relevance
“…Moreover, GCF collected from periodontitis patients contains activated complement fragments at higher concentrations than in GCF from healthy individuals [72, 7881]. Consistent with this, complement components and cleavage products are readily detected in chronically inflamed gingiva, whereas complement is undetectable or present at lower levels in healthy gingival biopsy samples [71, 73, 76, 77, 8284].…”
Section: Clinical Evidence Linking Complement To Periodontitismentioning
confidence: 87%
“…Moreover, GCF collected from periodontitis patients contains activated complement fragments at higher concentrations than in GCF from healthy individuals [72, 7881]. Consistent with this, complement components and cleavage products are readily detected in chronically inflamed gingiva, whereas complement is undetectable or present at lower levels in healthy gingival biopsy samples [71, 73, 76, 77, 8284].…”
Section: Clinical Evidence Linking Complement To Periodontitismentioning
confidence: 87%
“…Total activation (classic and alternate) may be assessed by C3 conversion and has been studied in GCF by means of an experimental gingivitis model. Patters et al (1985) found higher conversion levels in gingivitis than in normal tissues. In further studies, Patters et al (1989) measured C3c, a cleavage product of C3, in GCF from patients following extensive scaling and root planing treatment.…”
Section: Complementmentioning
confidence: 88%
“…Patters et al (1985) found higher conversion levels in gingivitis than in normal tissues. In further studies, Patters et al (1989) measured C3c, a cleavage product of C3, in GCF from patients following extensive scaling and root planing treatment. The decrease in clinical indices during repair was paralleled by a decrease in conversion ofC3toC3c.…”
Section: Complementmentioning
confidence: 88%
“…Activation products of the complement components have been detected in the gingival crevicular fluid at the site of gingival inflammation (Patters et al, 1989). C3d, an activation product of C3, is known to be present at high levels in the gingival crevicular fluid of AP patients, but not in serum, suggesting local activation of complement (Schenkein and Genco, 1977).…”
Section: Introductionmentioning
confidence: 99%